Interaction of the expression of two membrane genes, acrA and plsA, in Escherichia coli K-12. - Nakamura, H (1975)
The mutation acrA1, leading to acriflavine sensitivity through disorganization of the plasma membrane, is located between proC and purE on the Escherichia coli K-12 chromosome. Gene plsA has been reported to determine biosynthesis of membrane phospholipid and to be located very near acrA (1). Genes acrA and plsA fall into different cistrons and are arranged in the order proC-acrA-plasA-purE. The genes were shown to interact with each other. Introduction of acrA mutation into a plsA temperature-sensitive mutant mitigated the heat sensitivity. Plasmid (F-gal+) stability in acrA mutants was restored by introduction of the plasA mutation into the acrA cells. When an Hfr plsA donor was conjugated with an acrA recipient, or when reciprocally conjugated, the exogenotes were eliminated at high frequency during subsequent subcultivation in broth. However, the exogenotes were not eliminated in all other allelic combinations of genes acrA and plsA. When an F-gal+ plasmid was introduced into the unstable heterozygotes (acrA+plsA/acrApls1+), the plasmids were stably hosted, whereas the acrA+ plasA exogenotes were spontaneously lost at a high frequency. On the other hand, when the unstable heterozygotes carrying F-gal+ were cultured in acriflavine-containing medium, the F-gal+ plasmids were preferentially eliminated but the acrA+plasA exogenotes were not affected. The results suggest that the organization of the plasma membrane controls the recombination of the exogenotes introduced into zygotes.